KEDUDUKAN HUKUM ATAS PENCABUTAN KETERANGAN SAKSI DALAM UPAYA PENINJAUAN KEMBALI PERKARA PIDANA (STUDI KASUS PUTUSAN MAHKAMAH AGUNG NOMOR 1688 PK/PID.SUS/2024) - MANSUR, MANSUR (Fakultas Hukum Universitas Narotama, 2026)
This study examines the legal standing of revoking witness statements as new facts (Novum) in a judicial review (PK) effort, by analyzing the Ratio Decidendi of the Supreme Court (MA) in Decision Number 1688 PK/Pid.Sus/2024. Witness statements are fundamental evidence (Article 183 of the Criminal Procedure Code), so their revocation has the potential to undermine the basis of criminal evidence, but this also creates a conflict between the demands of material justice and the principle of legal certainty (res judicata). Using a normative juridical method, this study concludes that the evidence of testimony (witness/defendant) independently cannot be qualified as Novum. The statement must be further proven through a separate court process, where the Novum is the decision resulting from the evidence (referring to the Sengkon and Karta cases). The Ratio Decidendi of the MA in Decision Number 1688 PK/Pid.Sus/2024 rejected the revocation of the Liga Akbar Witness statement. The Supreme Court asserted that the revocation, carried out years after the verdict had become legally binding, while the initial testimony was given under oath, was